Utilization of the Canva Platform as a Project-Based Learning Strategy on Quranic Verses in Madrasah - Rosyidah, Laily; Syafi’i, Imam; Fahmi, Muhammad (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
In a time of ever-changing education, technology is essential for improving the learning experience. The objective of this research is to examine how the Canva platform is utilized as media for implementing project-based learning in the instruction of Qur’anic verses related to patience and optimism at MTs Bustanul Arifin, particularly in class VII A. The research method used a qualitative approach with a field research design. The subjects in this study consisted of 2 Islamic Religious Education teachers and 32 class VIIA students. Data were collected through observation, interview, and documentation techniques, then data analysis was carried out systematically through the stages of data condensation, data presentation, and conclusion drawing. Teachers act as the main informants in providing information related to the learning strategies used, while students become additional data sources through active participation in the observed learning process. The results suggest that Canva has the potential to boost student participation and curiosity by providing interactive and imaginative educational opportunities. Several obstacles were recognized, such as challenges in replicating Qur’anic text, a lack of design expertise, and time management difficulties when finishing the tasks. Nonetheless, implementing Canva as a project-based learning approach fosters the enhancement of 21st-century skills like critical thinking, teamwork, effective communication, and innovation, all while enhancing the quality of learning experiences. The study's findings suggest that incorporating technology into education can enhance students' comprehension of the subject matter more practically and contextually, leading to increased motivation and improved learning outcomes.